Use of ICT for Administration and Management: Case Study, EMU - Gedwar, Said (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Information Communication Technology is the most vital specialty in both working and educational environment, and newer drifts in higher educational researches are finding results regarding the usefulness of ICT towards facilitating education and work conditions for intending users. The major significance of this study is centered on the evaluation of ICT uses for the administration and management of educational institution; using EMU as a case study. This study investigated on the major importance of ICT to staff of EMU and also conducted a test to determine if significant difference exists between items and data variables such as age, gender, years of experience, usage of ICT tools, educational level, etc,. Information was collected from respondents via the use of questionnaire. 72 EMU staff was examined according to the various demographics of the study. Critical examination was made of the total data collected for this study by adopting ANOVA and t-test, frequency and percentages. Findings of this study shows that majority of the EMU staff agreed and strongly agree that ICT can be of pertinent help to them and also that ICT helps their work move smoothly and properly and in a timely manner. The study also goes to prove that male and female of EMU staff have different notions on their opinion on been comfortable when using ICT tools in their daily job. But more than 90% of the staff shows that no significant difference exist between male and female staff of EMU on their various uses of ICT for managing and administering education. Crosstabulations was further done on several significant points of the t-test and ANOVA test of the study, such as on gender and their comfortability when using ICT tools in their daily jobs, results showed that male held the larger paercentage as to the agrrement to the subject matter than their female counterparts. Keywords: Administration, Management Information and Communicatıon Technology

ÖZ: Bilişim İletişim Teknolojisi çalışma ve eğitim ortamının en önemli özelliğidir, ve eğitim alanındaki araştırmalar içerisindeki daha yeni eğilimler BİM’in niyetli kullanıcılar için eğitimi ve çalışma koşullarını kolaylaştırma alanında kullanışsızlığı ile ilgili sonuçlar bulmaktadır. Bu çalışmanın en büyük özelliği, DAÜ’yü örnek olay incelemesi olarak kullanarak BİM’in idare ve eğitim merkezleri yönetiminin gelişimi üzerinde yoğunlaşmasıdır. Bu çalışma BİM’in DAÜ çalışanları için en büyük önemi araştırmış ve maddelerin ve yaş, cinsiyet, yıllık deneyimleri, BİM kullanımı vb veri değişkenlerinin arasında önemli bir farkın olup olmadığını belirlemek için bir test yapmıştır. Bu veriler cevaplayıcılardan anket aracılığıyla toplanmıştır. Çalışmanın çeşitli toplumsal istatistiklerine göre 72 tane DAÜ çalışanı incelendi. Bu çalışma için elde edilen toplam veri ANOVA ve t-test, frekans ve yüzdeliklerle ciddi bir incelemeden geçti. Bu çalışma gösteriyor ki çoğu DAÜ çalışanı BİM’in onlar için uygun bir yardımcı olduğunu ve işlerinin rahatlıkla ve düzgün bir şekilde ve zamanında akması için yardımcı olduğunu şiddetle kabul etmişlerdir. Bu çalışma erkek ve kadın DAÜ çalışanlarının günlük işlerinde BİT kullanımı hakkında farklı görüşleri olduğunu da kanıtlamıştır. Ama çalışanların %90’ından fazlası erkek ve kadın çalışanların eğitimi uygulamak ve idare etmek için BİM kullanımı arasında önemli bir farkın olmadığımı göstermektedir. Çalışmanın T-test ve ANOVA testlerindeki cinsiyet ve günlük işlerde kullanılan BİM rahatlığı gibi çeşitli önemli noktalarda çapraz tablolama yapılmıştır ve sonuçlar erkek çalışanların kadın meslektaşlarına kıyasla mevzulara uyma konusunda daha büyük bir yüzdeliği oluşturduğunu göstermiştir.Anahtar Kelimeler: İdare, Bilişim İletişim Teknolojisi
Master of Science in Information and Communication Technology in Education. Thesis (M.Ed.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technology in Education, 2016. Supervisor: Assoc. Prof. Dr. Fahme Dabaj.
Keywords: Information and Communication Technology in Education; Education - Effect of technological innovations on - Eastern Mediterranean University - Cyprus, North; Educational technology - Information Technology - Eastern Mediterranean University - Cyprus, North; Educational Technology; Administration; Management Information; Communicatıon Technology; Educational technologies; performance; attitudes